Mining Discursive and Interactional Signals in Public Teleconsultation Platforms: A Deep Learning Approach to Referral Conduct Analysis - Santos, Diego S. N. dos; Cunha, Alvaro B.; Penna, Gustavo; Coelho, Frederico; Ferreira, Carlos H. G.; Torres, Luiz Carlos B. (Anais Estendidos do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS); 2026: Anais Estendidos do XXVI Simpósio Brasileiro de Computação Aplicada à Saúde, 2026)
Digital platforms used in public healthcare systems generate large volumes of interactional and discursive data. In the Brazilian Unified Health System (SUS), teleconsultation platforms mediate communication between primary care professionals and specialists, producing textual dialogues that encode referral requests, diagnostic uncertainty, collaborative decision-making, and operational patterns of care coordination. This paper investigates whether such digital and discursive signals can be mined to classify patient conduct as Retention in primary care or Referral to specialized care. Using 40,506 deidentified teleconsultation records from a Brazilian telehealth center, we evaluate Transformer-based models adapted to Portuguese clinical text, combining BioBERTpt, Head+Tail truncation, Focal Loss, and validation-based threshold selection. The final model achieved a Macro F1-Score of 0.61 and an accuracy of 71.2%, preserving predictive performance while shifting the validationoptimized threshold closer to the default probability boundary. Beyond aggregate performance, we conduct a post-hoc analysis across medical specialties, revealing statistically significant heterogeneity in model errors. These findings suggest that interprofessional teleconsultation logs can serve as a valuable source of digital and discursive signals for operational public health analysis, while also highlighting the need for subgroup evaluation, calibration-specific metrics, and external validation before any prospective deployment.